On the symbol-pair distances of repeated-root constacyclic codes of length 2ps - H. Q. Dinh (2019)
© 2019 Elsevier B.V. Let p be an odd prime, and λ be a nonzero element of the finite field Fpm. The λ-constacyclic codes of length 2ps over Fpm are classified as the ideals of quotient ring [Formula presented] in terms of their generator polynomials. Based on these generator polynomials, the symbol-pair distances of all such λ-constacyclic codes of length 2ps are obtained in this paper. As an application, all MDS symbol-pair constacyclic codes of length 2ps over Fpm are established, which produce many new MDS symbol-pair codes with good parameters.